2016
DOI: 10.17576/gema-2016-1603-01
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Analysis of Discourse Particles in Filipino Computer Mediated Communication

Abstract: As the English language continues to evolve through time, many of its structures and functions changed, which made it even realizable that the smallest unit in a discourse can play a crucial role in communication. Hence, this present study is an attempt to investigate the phenomenon and further delve into the discourse-pragmatic functions of discourse particles (DPs) in digital genres, particularly on Facebook, since DPs are commonly used by Filipino youths when posting and commenting online. Thirty tertiary-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
3
16
0
3
Order By: Relevance
“…In spite of the fact that associations of some subjects did not reflect the interpretation of the target idiom it was the target idiom that they relied upon when completing the situation. Thus, it confirmed the idea that every unit in a discourse (even the smallest one) can play a crucial role in communication (Palacio & Gustilo 2016). Let's look at it.…”
Section: The Associations With the Text Situation It Does Not Matter supporting
confidence: 75%
“…In spite of the fact that associations of some subjects did not reflect the interpretation of the target idiom it was the target idiom that they relied upon when completing the situation. Thus, it confirmed the idea that every unit in a discourse (even the smallest one) can play a crucial role in communication (Palacio & Gustilo 2016). Let's look at it.…”
Section: The Associations With the Text Situation It Does Not Matter supporting
confidence: 75%
“…Though sharing similar trivialities like that of discourse particles, the functions of these languages are of prominence in the game narrative and mechanics. In the perspectives of video games as computer mediated communicators, these prominent functions are in line with what Palacio and Gustilo (2016) Tales of the Abyss, and Solaris in Xenogears. These fictional game conlangs are plot drivers and story relays in their games and, in the perspectives that any languages within a fiction are fictional conlangs, they co-exist with fictional game conlangs functioning as lingua franca in the fictional world.…”
Section: Findings a Priori And A Posteriori Weaknessmentioning
confidence: 57%
“…The orders of elements of arguments might be varied. The research results also showed that there were various pragmatic meanings found in the arguments used by the president and vice-president candidates (Palacio & Gustilo, 2016). The results of the study which was analyzed using the critical pragmatic perspective reflect how far the candidates were concerned with the marginalized, the underprivileged, and the subjugated people.…”
Section: R E S E a R C H H I G H L I G H T Smentioning
confidence: 86%